Modified Explicit Scheme for Solving Neutrosophic Fuzzy Heat Equation - Hamzeh Zureigat (Neutrosophic Sets and Systems)
In this paper, an explicit finite difference method is developed and applied for the first time to solve the neutrosophic fuzzy heat equation. For this purpose, the triangular neutrosophic number is used in both the neutrosophic exact and numerical solution. In addition, solutions of neutrosophic fuzzy heat equation were observed at the (𝛼, 𝛽, 𝛾)-cut with varied time scales. Also, the error between the analytical and numerical solution obtained on the (𝛼, 𝛽, 𝛾)-cut is evaluated and illustrated. A good amount of agreement is seen using closed-form and numerical solutions.